Edukasi Menstruasi untuk Meningkatkan Pemahaman Fiqh Wanita Dasar pada Anak-anak di Dusun Ngambar Gresik - Muchammad Catur Rizky; Khoirun Niswatin; Wanda Citra Dewi (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service aims to provide education on menstruation to enhance the basic understanding of women’s fiqh for children in the Ngambar village of Gresik. The method used is the PAR (Participatory Action Research) method which includes counseling, direct demonstrations, and discussions. The results of the activities show that the children in Ngambar village, who previously had a limited understanding of the basic concepts of menstruation and the related Islamic laws, experienced a significant increase in understanding after participating in this educational activity. This menstruation education program can create awareness about the importance of maintaining hygiene, understanding the menstrual cycle counts, as well as understanding the prohibitions of prayer and fasting during menstruation, how to purify oneself after menstruation, and also boost their confidence, while preparing the children mentally for the menstruation period